Pengaruh Kinerja Ekonomi dan Kinerja Lingkungan Hidup Terhadap Nilai Perusahaan - Arif Darmawan; Mutiara Zahrani (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This study explores the relationship between economic and environmental performance and firm value in the consumer non-cyclical sector listed on the Indonesia Stock Exchange during 2020–2023. The sample consists of companies that consistently published sustainability reports. Economic performance is measured using Economic Value Added (EVA) is a comprehensive and to reflect long-term value creation, Meanwhile, environmental performance is evaluated based on ESG ratings published by the BGK Foundation. To determine firm value, Tobin’s Q is used as the main indicator, with leverage introduced as a control factor to account for capital structure influence. A quantitative method is employed, utilizing secondary data. A total of 18 companies were purposively selected, resulting in 72 observations over four years. The analysis uses panel data regression, beginning with descriptive statistics, followed by model selection, classical assumption tests, and hypothesis testing. The findings indicate that EVA has a significant positive effect on firm value, suggesting that strong economic performance enhances market valuation. In contrast, ESG scores are found to negatively influence firm value, implying that higher environmental disclosures may not align with investor expectations in this context. Simultaneous testing confirms the overall significance of the independent variables, while leverage does not show a notable impact.